PERAN TEKNOLOGI INFORMASI TERHADAP SISTEM PENGENDALIAN INTERN DI RUMAH SAKIT UMUM PUSAT PROF. DR. R.D. KANDOU MANADO - Meifa Julia Punu; Lintje Kalangi; Jessy D. L. Warongan (Universitas Sam Ratulangi, 2022)
This research aims to analyze the role of information technology on internal control systems in Prof. Dr. R. D. Kandou Manado Central General Hospital. This research is qualitative research with confirmatory analysis approach in case study through in semi-structured interviews, observation and documentation studies. The results of this research is related with implementation of Government Regulation Number 60 of 2008 about Government Internal Control Systems. The role information technology can facilitate management in decision making, cooperative relationships, and performance efficiency. The implementation of internal control elements in the role of information technology are still have problems in the monitoring and control elements, the problems are the entry of inventories, accounts receivables, and accounts payable are inaccurate and not punctual because the information technology in the hospital has not been fully integrated. The obstacles that cause the information technology has not fully integrated and has not role on internal control optimally are on the role human resources. Neither managements nor internal auditors have initiative to solve control activities problems. Inadequate competences of internal auditors, limited educational background from information system hospital employees has effect in limitation understanding hospital business process